Solution for instability in magnetizing of toroidial coil winding - Ahmad Azwan, Abdul Razak (2016)
This thesis described the solution for problem of instability of magnetizing process occurred to the current process. It was done at Universiti Malaysia Pahang from Faculty of Manufacturing and Vacuumschmelze (M) Sdn. Bhd. Pekan. The objective of the study is to define an improvement or solution to the problem of the current process that affect the products unit. The survey, observation, experiment and data recording were done at the company by visiting their production line. The data were then recorded and further analyzed for the determination of the real situation and what actually happen to the current process which lead to the uninform of the boundaries, angles and inductance of the toroidal coil. After the problem was determined, the solution then created. A machine, called as low cost semiautomated winding machine was design. Before the system finished some modification and suggestion were brought to the board to ease the operators do the process, including solution to the problem that they faced every day. The system created as the initial problem solution while the machine was finished to be fabricated. The machine design then created using software for all of its component including mechanical, electrical and electronics and programming. The machine then tested and the result compared to the result of the current process. For the comparison, the machine improved a lot of the units' criteria, and only few of the unit were rejected. The inductance or the main problem faced by the current process also very much improved as the graph of the tested unit show it can functioning at the required ranges of induction value. However, there are some weakness of the machine that needed to be accounted as improvement in the future.